Acroscyphodysplasia as a phenotypic variation of pseudohypoparathyroidism and acrodysostosis type 2. Issue 10 (10th July 2014) - Mitsui, Toshikatsu; Kim, Ok‐Hwa; Hall, Christine M.; Offiah, Amaka; Johnson, Diana; Jin, Dong‐Kyu; Toh, Teck‐Hock; Soneda, Shun; Keino, Dai; Matsubayashi, Shohei; Ishii, Tomohiro; Nishimura, Gen; et al.
Abstract : Acroscyphodysplasia (OMIM250215) is a distinctive form of metaphyseal dysplasia characterized by the distal femoral and proximal tibial epiphyses embedded in cup‐shaped, large metaphyses known as metaphyseal scypho ("scypho" = cup) deformity. It is also associated with severe growth retardation and brachydactyly. The underlying molecular mechanism of acroscyphodysplasia has not yet been elucidated, although scypho‐deformity of the knee has been reported in three patients with acrodysostosis due to a mutation in the PDE4D gene. We report on the clinical, radiological, and molecular findings of five female patients with acroscyphodysplasia; two were diagnosed as pseudohypoparathyroidism (PHP) or Albright hereditary osteodystropy, and the other three as acrodysostosis. They all had radiological findings consistent with severe metaphyseal scypho‐deformity and brachydactyly. Heterozygous mutations were identified in the PHP patients consisting of one novel (p.Q19X) and one recurrent (p.R231C) mutation of the GNAS gene, as well as, in the acrodysostosis patients consisting of two novel mutations (p.T224I and p.I333T) of the PDE4D gene. We conclude that metaphyseal acroscyphodysplasia is a phenotypic variation of PHP or acrodysostosis caused by either a GNAS or PDE4D mutation, respectively. © 2014 Wiley Periodicals, Inc.